1996
DOI: 10.1046/j.1365-2133.1996.d01-1101.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis in south-east London-a new pattern of infection with public health implications

Abstract: Recent observations on tinea capitis cases in London suggest that there has been a change in the pattern of infection with a recent and significant rise in the incidence of infections due to anthropophilic fungi. The purpose of this study was to investigate the prevalence and identity of tinea capitis in schools in south-east London and factors which might affect the spread of infection. This was achieved by carrying out a survey of all children, with parental consent for scalp examination, in 14 nursery, infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
137
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 10 publications
10
137
1
3
Order By: Relevance
“…However in the United Kingdom [7] the most prevalent species is T. tonsurans, while in France [2] those are T. soudanense and M. audouinii. Nevertheless in these European countries it was found that the zoophilic species such as M. canis, T. mentagrophytes and T. verrucosum are the most frequentely isolated dermathophytes from the material of patientes who live in rural areas [1][2][3][4][7][8][9][10]. Epidermophyton flocossum, was detected in a significant percentage as the cause of superficial mycosis in Finland and Germany [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However in the United Kingdom [7] the most prevalent species is T. tonsurans, while in France [2] those are T. soudanense and M. audouinii. Nevertheless in these European countries it was found that the zoophilic species such as M. canis, T. mentagrophytes and T. verrucosum are the most frequentely isolated dermathophytes from the material of patientes who live in rural areas [1][2][3][4][7][8][9][10]. Epidermophyton flocossum, was detected in a significant percentage as the cause of superficial mycosis in Finland and Germany [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…By evaluating numerous studies of a large group of authors, it is discovered that the most comon cause of superficial mycosis in European countries are the species T. rubrum, M. canis, T. mentagrophytes var granulosum and T. verrucosum [7][8][9][10]. Species M. audouinii, T. soudanense and T. violaceum, causes of so-called immigrational mycosis, can rarely be detected in this area of our continent, considering the fact that endemic zones for these species are in Africa and some regions of Asia [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Prävalenz für die USA wird mit 3-8% der Gesamtbevölkerung angegeben [53]. Daten aus dieser Region sowie Großbritannien belegen eine Zunahme der Erkrankungsfälle, insbesondere in Hinblick auf eine durch Trichophyton tonsurans bedingte Kopfpilzerkrankung [27,36].…”
Section: Schlüsselwörterunclassified